Justice as a Category of Canonical Law - Leszczyński, Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The justice system, based on human dignity, but also resulting from the fact of baptism, poses a challenge in properly defining and understanding the relationship between the state and the Church, in which the same person is both a faithful of the Church and a citizen of the state.